A CLINICAL CASE OF LOBULAR CAPILLARY HAEMANGIOMA OF THE NASAL CAVITY DURING PREGNANCY - Lutfullaev G.U., Nematov O.S., (Central Asian Journal of Medicine, 2025)
A benign lesion called a lobular capillary haemangioma originates in the vascular tissue of the skin, mucosa, muscles, glands, and bones. These lesions spread quickly. Rarely occurs nasal localization. Pregnancy and microtrauma are the two most frequently suggested aetiological reasons. Pregnancy-related incidence has been reported to range from less than 2% to roughly 5%. Depending on the severity of the symptoms and the stage of the pregnancy, the treatment of a pregnant woman with such a lesion may be complicated. The preferred course of treatment is complete surgical excision, either with or without pre-operative embolization.